Measuring Outsourcing Performance of Malaysian Economic Transformation Program - Hassan, Mohamad Ghozali; Abdullah, Rohani; Razalli, Mohd. Rizal (Society for Alliance, Fidelity & Advancement, 2016)
The focus of this research is to find out the strategic relationship among the environmental dynamism, outsourcing success, and the performance of the relationship. Data was collected by postal survey from electrical and electronic manufacturing industries in Malaysia. In general, the results of multiple regressions indicated support for strategy relationships factor and outsourcing success. Finally, hierarchical regression analysis was carried out to determine the moderating effect of environmental dynamism on outsourcing success. The result of the study indicated full support of these moderating effects. This paper presents a useful source of information for practitioners who seeks to improve the outsourcing performance